Gambaran Pelaku Riba Perspektif Al-Qur’an - Abdul Syukkur (STAI Al-Mujtama Pamekasan, 2023)
The Qur'an calls the perpetrator of usury like a dazed person in the afterlife, because he does not have a firm foothold, so he is unable to support his body and staggers. This kind of image of usury perpetrators is proof that usury behavior is very bad. This research provides a description of how bad the fate of usury perpetrators is in the Qur'an, by collecting verses from the Qur'an about the description of usury perpetrators, mentioning the interpretation of the mufassir, describing the whole picture and complementing it with the hadiths of the Prophet Muhammad SAW. The conclusion of this study gets the idea that the perpetrator of usury will not rise from his grave at the end of the world, other than to exist in a state like a strangled madman, and another picture of punishment in the afterlife. Keywords: Usury, Overview, Qur'an